Effect of Spirulina on growth, immunity, gut bacterial load and histopathology of broiler birds - Sethy, Kamdev; KHADANGA, ARPITA; SETHY, K; SAMANTARAY, S M; RAY, P; PANDA, N; MISHRA, S K; NAIK, M; TRIPATHY, S (The Indian Journal of Animal Sciences, 2023)
This study was carried out to evaluate the effects of Spirulina on growth, immunity, gut microbiome, and important organ histopathology in Vencobb broilers. 160 day-old chicks were randomly assigned to four diets. T0: basal diet, T1: basal diet + Spirulina (0.50% of basal diet), T2: basal diet + Spirulina (1.0% of basal diet), T3: basal diet + Spirulina (1.50% of basal diet). The experimental period was 35 days. Body weight change was measured at weekly intervals. Humoral immunity, cellular immunity, lymphoid organ mass, histopathology, intestinal bacterial load and intestinal morphology were measured on the 35thday of the experimental feeding period. Body weights were significantly higher in all treated birds than in control. Lymphatic organ weights, HI titers and CBH responses in the various treatment groups were significantly higher than those in the control group. The total bacteria (log10cfu/ml), Escherichia coli and Salmonella counts in the intestinal contents were significantly lower in the Spirulina treated group than in the control group, and the intestinal Lactobacillus count was higher in the treated birds than in the control group. The villi length and width of the treated birds were significantly greater than those of the control group. Histopathology studies have shown that Spirulina @ 1.5% of the basal diet have no detrimental effect on the bird’s liver and kidneys. It can be concluded that adding 1.50% Spirulina to the diet of Vencobb broilers improves growth, immunity and reduces gut microbial load.